2018
DOI: 10.3389/fpls.2018.00781
|View full text |Cite|
|
Sign up to set email alerts
|

The Vacuolar Protein Sorting-38 Subunit of the Arabidopsis Phosphatidylinositol-3-Kinase Complex Plays Critical Roles in Autophagy, Endosome Sorting, and Gravitropism

Abstract: The family of phosphatidylinositols (PtdIns) plays essential roles in membrane identity and intracellular trafficking events. In animals and yeast, PtdIn-3-phosphate, which is particularly important for endosomal sorting, lysosomal/vacuolar transport and autophagy, is assembled by two conserved kinase complexes comprised of the catalytic VACUOLAR PROTEIN SORTING (VPS)-34 subunit, along with VPS15, AUTOPHAGY-RELATED (ATG)-6, and either ATG14 (complex I) or VPS38 (complex II). Here, we describe the Arabidopsis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 81 publications
2
19
0
Order By: Relevance
“…In our study, the upregulated gene (Zm00001d048258) encoding phosphoinositide phosphatase SAC2 was targeted by the downregulated sbi-miR5381_L-1R+3, which indicated that miR5381 is involved in signaling transduction under HT stress. Moreover, another upregulated gene encoding vacuolar protein sorting-associated protein 24 (VPS24) homolog 1 was targeted by the downregulated miRn202 (Table S8) and VPS24 homolog 1 was enriched in vacuolar transport and the endocytosis pathway, which is consistent with a recent report that identified it as one subunit of the Arabidopsis phosphatidylinositol-3-kinase complex, in which the VPS38 plays critical roles in autophagy and endosome sorting [65].…”
Section: Discussionsupporting
confidence: 86%
“…In our study, the upregulated gene (Zm00001d048258) encoding phosphoinositide phosphatase SAC2 was targeted by the downregulated sbi-miR5381_L-1R+3, which indicated that miR5381 is involved in signaling transduction under HT stress. Moreover, another upregulated gene encoding vacuolar protein sorting-associated protein 24 (VPS24) homolog 1 was targeted by the downregulated miRn202 (Table S8) and VPS24 homolog 1 was enriched in vacuolar transport and the endocytosis pathway, which is consistent with a recent report that identified it as one subunit of the Arabidopsis phosphatidylinositol-3-kinase complex, in which the VPS38 plays critical roles in autophagy and endosome sorting [65].…”
Section: Discussionsupporting
confidence: 86%
“…Vacuolar traffic and autophagy are important in homeostasis and detoxification processes but are often interconnected to ER and GA plasticity and involve the formation of the so-called Multi Vesicular Bodies (MVBs) [80][81][82][83][84][85]. A microarray study in Populus stressed by Zn allowed the identification of an AQP of NIP type, AQUA1 [86], down-regulated in both leaf and root tissues, possibly with the effect to reduce transpiration, water/Zn uptake, and leaf growth, probably for protecting photosynthetic tissues and for enhancing poplar tolerance [87].…”
Section: Multi-vesicular Bodiesmentioning
confidence: 99%
“…We suggest that NIP1;1 can increase translocation of As(III), coherently with its localization in the ER, but it has a prominent role in intracellular compartmentalization so that its absence alters the vacuole characteristics and, as a consequence, As(III) tolerance. The different involvement of vacuolar traffic machineries in homeostasis and detoxification processes and the connections with autophagy have been previously studied (Kulich and ŽårskĂ˝, 2014; Sharma et al, 2016; Barozzi et al, 2017; Faraco et al, 2017; Ariani et al, 2018; Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%